2009
DOI: 10.1017/s095442240926402x
|View full text |Cite
|
Sign up to set email alerts
|

When nutrition interacts with osteoblast function: molecular mechanisms of polyphenols

Abstract: Recent research has provided insights into dietary components that may optimise bone health and stimulate bone formation. Fruit and vegetable intake, as well as grains and other plant-derived food, have been linked to decreased risk of major chronic diseases including osteoporosis. This effect has been partially attributed to the polyphenols found in these foods. Thus, it has been suggested that these compounds may provide desirable bone health benefits through an action on bone cell metabolism. The present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 124 publications
1
63
0
Order By: Relevance
“…[1,6] In addition, other specific nutrients, foods, or dietary patterns can influence bone health. [6][7][8][9] Adhering to a traditional Mediterranean diet (MedDiet), characterized by high intake of fruits, vegetables, nuts and olive oil, has been linked to a lower risk of hip fractures, [10][11][12] which might partly explain the epidemiological evidence of a geographical variation in the incidence of hip fractures across Europe, the highest rates being in North Europe and the lowest in the Mediterranean basin countries or in United States' population where it was associated a lower risk of hip fracture with MedDiet pattern. [11,13] These observations might be attributed to the high content of monounsaturated fats (MUFA) and polyphenols in olive oil, the main fat consumed in the Mediterranean diet.…”
Section: Introductionmentioning
confidence: 99%
“…[1,6] In addition, other specific nutrients, foods, or dietary patterns can influence bone health. [6][7][8][9] Adhering to a traditional Mediterranean diet (MedDiet), characterized by high intake of fruits, vegetables, nuts and olive oil, has been linked to a lower risk of hip fractures, [10][11][12] which might partly explain the epidemiological evidence of a geographical variation in the incidence of hip fractures across Europe, the highest rates being in North Europe and the lowest in the Mediterranean basin countries or in United States' population where it was associated a lower risk of hip fracture with MedDiet pattern. [11,13] These observations might be attributed to the high content of monounsaturated fats (MUFA) and polyphenols in olive oil, the main fat consumed in the Mediterranean diet.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the aromatic compounds, flavonoids and tannins are most commonly found in plant organs [43]. As previously reviewed by Habauzit & Horcajada [44], polyphenols can act on bone metabolism by modulating osteoblast proliferation, differentiation and mineralization, as well as osteoclast function [45].…”
Section: Quercus Infectoriamentioning
confidence: 99%
“…These precursors are multipotent mesenchymal stem cells that can be differentiated into several kinds of tissue specific cells such as osteoblasts, myoblasts, adipocytes and chondrocytes [45]. Bone formation is a tightly regulated process which is characterized by a sequence of events starting with the commitment of osteoprogenitor cells, their differentiation into pre-osteoblasts and finally mature osteoblasts whose function is to synthesize bone matrix that becomes progressively mineralized.…”
Section: The Osteoblastmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher consumption of fruits and vegetables has been correlated with a reduction in the risk for the development of osteoporosis. (Arikan et al, 2011;Prentice et al, 2006;Macdonald et al, 2004;Macdonald et al, 2008;Palacios et al, 2006;Tucker et al, 1999;Lister et al, 2007;New, 2003;Trzeciakiewicz et al, 2009 Numerous studies have shown the health-promoting properties of polyphenols, providing additional mechanisms through which they promote skeletal health by reducing resorption caused by high oxidative stress (Trzeciakiewicz et al, 2009;Tucker, 2009;Hunter et al, 2008). The antioxidant properties of polyphenols have been widely studied and reported in the literature (Liu et al, 2005;Miyamoto et al,1998;Rassi et al, 2002;Viereck et al, 2002;Ward et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%